Semantic cues enhanced multimodality multistream CNN for action recognition - Tu, Zhigang (2020)
This paper addresses the issue of video-based action recognition by exploiting an advanced multistream convolutional neural network (CNN) to fully use semantics-derived multiple modalities in both spatial (appearance) and temporal (motion) domains, since the performance of the CNN-based action recognition methods heavily relates to two factors: semantic visual cues and the network architecture. Our work consists of two major parts. First, to extract useful human-related semantics accurately, we propose a novel spatiotemporal saliency-based video object segmentation (STS) model. By fusing different distinctive saliency maps, which are computed according to object signatures of complementary object detection approaches, a refined STS maps can be obtained. In this way, various challenges in the realistic video can be handled jointly. Based on the estimated saliency maps, an energy function is constructed to segment two semantic cues: the actor and one distinctive acting part of the actor. Second, we modify the architecture of the two-stream network (TS-Net) to design a multistream network that consists of three TS-Nets with respect to the extracted semantics, which is able to use deeper abstract visual features of multimodalities in multi-scale spatiotemporally. Importantly, the performance of action recognition is significantly boosted when integrating the captured human-related semantics into our framework. Experiments on four public benchmarks-JHMDB, HMDB51, UCF-Sports, and UCF101-demonstrate that the proposed method outperforms the state-of-the-art algorithms.